2019
DOI: 10.1159/000497110
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Predictive Value of High-Grade Squamous Intraepithelial Lesion on Cytology for the Histological Diagnosis of Cervical Intraepithelial Neoplasia 2 or Higher: A Systematic Review

Abstract: Cervical cancer is a major worldwide health problem. Therefore, regular cervical screening in order to make an early diagnosis can help to prevent cervical cancer, through identifying and treating preinvasive cervical lesions. The aim of this review is to evaluate the correlation between the cytological screening result and the final gold standard histological outcome in the diagnosis of cervical lesions. More specifically, the correlation between high-grade intraepithelial lesion (HSIL) on cytology and histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Cytology is an established technology for the detection of cancers and their precursors, for example of the bladder 31 , lung 32 and cervix 33 . Recent years have witnessed innovative solutions to the detection of Barrett's oesophagus 34 and oral cancer 35 using cytology, offering hope for early detection strategies 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Cytology is an established technology for the detection of cancers and their precursors, for example of the bladder 31 , lung 32 and cervix 33 . Recent years have witnessed innovative solutions to the detection of Barrett's oesophagus 34 and oral cancer 35 using cytology, offering hope for early detection strategies 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cytology is the main screening test in the South African public healthcare sector. This retrospective study of 344 women 19,20 Further studies have shown histologically confirmed CIN2+ ranging between 50% and 77%. [21][22][23] Additionally, a few studies have shown a decrease in PPV of HSIL cytology to detect CIN2+ after receiving the HPV vaccine.…”
Section: Discussionmentioning
confidence: 92%
“…In current clinical practice, the tools used for cervical cancer screening and diagnosis include HPV testing, cytology testing, colposcopy and cervical biopsy. Although combinations of different techniques have improved the screening and diagnosis of cervical cancer, the sensitivity, specificity, reliability and repeatability are still unsatisfactory due to sampling errors and/or screening errors, and the final diagnosis is still dependent on cervical biopsy (36). Thus, the development of a sensitive, non-invasive approach for the screening and diagnosis of HSILs and LSILs is essential to complement existing techniques.…”
Section: Discussionmentioning
confidence: 99%